Treatment of pneumoempyema with use of mini-invasive methods - Komarchuk, V. (Journal of Education, Health and Sport, 2017)
In this work we considered in detail and evaluated, the results of treatment of 77 patients with pneumoempyema by the method of thoracoscopy in combination with endoscopic bronchial blocking by a non-return valve.